Menelusuri Ragam Aktivitas Fisik Manusia Pendukung Situs Gilimanuk Bali Berdasarkan Markers Of Occupational Stress - Dicky Caesario Wibowo (Badan Riset dan Inovasi Nasional, 2022)
So far, numerous studies have investigated the Gilimanuk site's archaeological remains. This study seeks to use evidence of occupational stress in human skeletal remains to provide an overview of the physical activities that likely occurred at the Gilimanuk site. A total of 212 long bone samples were examined for markers of occupational stress. These pathological alterations could provide an explanation for certain physical activities. The results suggest that the type of human physical activity observed at the site is not closely related to seafaring activities. These findings are then integrated with other data such as artifacts, ecofacts, and the environmental setting to discuss the interaction of the human occupation of the Gilimanuk site with the surrounding environment.